2014
DOI: 10.1128/aem.03535-13
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Feedback Inhibition of Phosphoenolpyruvate Carboxylase for Improved Lysine Production in Corynebacterium glutamicum

Abstract: Allosteric regulation of phosphoenolpyruvate carboxylase (PEPC) controls the metabolic flux distribution of anaplerotic pathways. In this study, the feedback inhibition of Corynebacterium glutamicum PEPC was rationally deregulated, and its effect on metabolic flux redistribution was evaluated. Based on rational protein design, six PEPC mutants were designed, and all of them showed significantly reduced sensitivity toward aspartate and malate inhibition. Introducing one of the point mutations (N917G) into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 27 publications
(34 reference statements)
1
76
0
4
Order By: Relevance
“…Thus, we considered D299N an effective amino acid substitution for feedback-inhibition desensitization in PEPC from both ATCC14067 and ATCC 13032 strains. Interestingly, the location of this amino acid substitution differed from those identified recently by Chen et al (13) as effective substitutions for PEPC desensitization in lysine-producing ATCC 13032 derivatives, i.e., R620G, K653G, K813G, S869G, R873G, and N917G (around position of 600e900).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, we considered D299N an effective amino acid substitution for feedback-inhibition desensitization in PEPC from both ATCC14067 and ATCC 13032 strains. Interestingly, the location of this amino acid substitution differed from those identified recently by Chen et al (13) as effective substitutions for PEPC desensitization in lysine-producing ATCC 13032 derivatives, i.e., R620G, K653G, K813G, S869G, R873G, and N917G (around position of 600e900).…”
Section: Resultsmentioning
confidence: 49%
“…Thus, the overexpression of ppc does not necessarily lead to increased PEPC activity in C. glutamicum. In fact, recent studies demonstrated that a release of feedback inhibition of PEPC by aspartate/malate resulted in enhanced lysine production (13), suggesting that the release of feedback control in PEPC is another target to be considered for strain improvement not only for lysine producers but also for other amino acid producers. In this context, the effect of feedback inhibition-resistant PEPC on glutamic acid production under biotin-limited conditions needs to be clarified using wild-type C. glutamicum as the parent to understand the basic physiology of this industrially important bacterium.…”
Section: Feed-back Inhibition]mentioning
confidence: 98%
“…In contrast to many other organisms, C. glutamicum possesses a PEP carboxylase (Pck) together with a pyruvate carboxylase (Pyc) as anaplerotic enzymes. In the genome of a classical producer, the Pyc-P458S protein was identified as an advantageous mutein increasing L-lysine production (Ohnishi et al 2002), and deregulation of feedback inhibition of PEP carboxylase by aspartate and malate proved to increase L-lysine synthesis, too (Chen et al 2013). Aside from the two C3-carboxylating enzymes, C. glutamicum possesses three C4-decarboxylating enzymes converting oxaloacetate or malate to PEP or pyruvate, i.e., PEP carboxykinase, malic enzyme, and oxaloacetate decarboxylase.…”
Section: Increase Of Precursor Supplymentioning
confidence: 98%
“…Based on dynamic correlation analysis, a new algorithm was developed and utilized to discover residues that mediated the anticooperative process with high probability. Chen et al [36,37] took aspartokinase, an important allosteric enzyme for industrial amino acids production, as a model system, and a predictive approach combining protein dynamics and evolution was demonstrated for rational reengineering of enzyme allostery. In this method, molecular dynamic simulations of aspartokinase and statistical coupling analysis of protein sequences of the aspartokinase family were combined to identify a cluster of residues which are correlated during protein motion and coupled during the evolution.…”
Section: Elucidation Of Signal Transduction Pathwaysmentioning
confidence: 99%